Kaum Awam Dalam Era Disrupsi - Hironimus Bandur (STIPAS St. Sirilus Ruteng, 2018)
The word disruption is increasingly familiar to the ears of these millennial and tencenial, although Clay Christensen has published the disruption theory since 1997. The background of its emergence is the changing world situation and disturbing the life order of society. Disruption theory was born amid the frenetic changes due to the technological revolution, especially the internet. The Internet affects the dynamics of human life in almost every aspect: education, economics, commerce, social, political, cultural and religious. In the field of education found the pattern and system of education is constantly changing; in the field of economy and trade found the mechanisms of market and trade economies that differ greatly from the period before millennial and tensenial. In the field of religion, a change in the way of view of religion through subjective interpretations to interfere with the understanding of the average person about the substance of religion itself. In this changing society situation, all elements of society can challenge it but can not defeat it. In the Catholic Church, for the sake of the development of the Church, in addition to pastors, laymen are required to have certain characters such as reformers, literate technology literacy, creative, innovative and critish and inclusive.